2007
DOI: 10.2753/jec1086-4415120101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Personality Traits and Optimum Stimulation Level on Text-Messaging Activities and M-commerce Intention

Abstract: Mobile phones provide the freedom to participate in a variety of communication styles, ranging from simple voice-based communications to advanced text-messaging services. The decision to perform complex usage activities is determined by the interrelations of three personality traits. Using the optimum stimulation framework, the study hypothesizes that personal innovativeness and individual playfulness increase an individual's optimum stimulation level (OSL). Survey data from 246 text-messaging users showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 78 publications
1
55
0
1
Order By: Relevance
“…Extraverts tend to be impulsive and activity-seeking, and to yearn for sensory excitement; perhaps this tendency may affect their shopping activity on the mobile web. However, our finding is consistent with that of previous researchers, who demonstrated that the degree of environmental stimulation that individuals desired positively influenced their m-commerce intentions (Mahatanankoon, 2007).…”
Section: Discussion and Managerial Implicationssupporting
confidence: 83%
“…Extraverts tend to be impulsive and activity-seeking, and to yearn for sensory excitement; perhaps this tendency may affect their shopping activity on the mobile web. However, our finding is consistent with that of previous researchers, who demonstrated that the degree of environmental stimulation that individuals desired positively influenced their m-commerce intentions (Mahatanankoon, 2007).…”
Section: Discussion and Managerial Implicationssupporting
confidence: 83%
“…Van tions and music when users receive advertising will influence their BI level if they feel pleasurable. In the context of mobile 232 commerce, consumers are attributed to enjoyment rather than functional performance on searching products and services 233 via m-devices (Mahatanankoon, 2007). In line with above discussion, we suggest that the acceptance of m-advertising will 234 be influenced by individual's perception in pleasure and enjoyment from using the system.…”
Section: Effort Expectancy (Ee)mentioning
confidence: 80%
“…It has been argued that the acceptance of a mobile marketing message is likely to be influenced by consumers' personal predispositions, tendencies, attitudes and individual-level perceptions (Bhatti, 2007;Hsu, Lu, & Hsu, 2008;Junglas, Johnson, & Spitzmüller, 2008;Khalifa & Shen, 2008;Luarn & Lin, 2005;Mahatanankoon, 2007;Marez, Vyncke, Berte, Schuurman, & Moor, 2007;Pagani, 2004;Pedersen, 2005;Wang, Lin, & Luarn, 2006;Wu & Wang, 2005;Yang, 2005), demographics (Bigne, Ruiz, & Sanz, 2005;DeBaillon & Rockwell, 2005;Hanley, Becker, & Martinsen, 2006;Karjaluoto, Lehto, Leppäniemi, & Jayawardhena, 2008;Suoranta & Mattila, 2004), social/peer influence (Kim, Lee, & Kim, 2008;Lee & Murphy, 2006;Newell & Meier, 2007;Rohm & Sultan, 2006), cultural dimensions (Gressgard & Stensaker, 2006;Harris, Rettie, & Kwan, 2005;Lee, Kim, Lee, & Kim, 2002;Muk, 2007;Sultan & Rohm, 2008;Sundqvist, Frank, & Puumalainen, 2005;Weitenberner et al, 2006), acceptance of the mobile medium itself (Bigné, Ruiz, & Sanz, 2007;Heinonen & Strandvik, 2007), the relevance and the credibility of the content (Choi, Seol, Lee, Cho, & Park, 2008;Haghirian & Inoue, 2007;Karjaluoto, Standing, Becker, & Leppaniemi, 2008;Okazaki, 2004;Wang et al, 2006), the level of trust towards the message se...…”
Section: M-marketing Adoption and Acceptancementioning
confidence: 99%